Raeder’s Syndrome “Paratrigeminal Neuralgia” Beyond Headache: A Case Report - Gülnur Tekgöl Uzuner (Türk Nöroloji Dergisi, 2017)
Raeder’s syndrome (paratrigeminal neuralgia), which sometimes radiates to the maxillary section, is defined as a constant and unilateral pain in the distribution area of the ophthalmic branch of the trigeminal nerve accompanied by Horner’s syndrome and caused by a defect in the carotid artery or in the middle cranial fossa. Although Raeder’s syndrome is accompanied with the irritation of the trigeminal nerve, it can be easily confused with Horner’s syndrome and mistakenly called “painful Horner’s syndrome”. This picture, which contains incomplete Horner’s syndrome with orbital pain and without anhydrosis, is an important clinical entity because it shows the location of the lesion and is different from the etiologic and prognostic perspective. Due to these reasons, we wanted to present a patient who was diagnosed as having paratrigeminal oculosympathetic Raeder syndrome in our clinical department of neurology to draw attention to differences in underlying resemblance to Horner’s syndrome